THE ROLE OF ISLAMIC ECONOMICS IN SUSTAINABLE DEVELOPMENT GOALS - Nurul Hidayah; Dona Santika; Zaitul Ummi; Riza Arifin; Siti Rifani (Proceeding International Seminar of Islamic Studies, 2023)
Islamic economics is a science that seeks to view, review, examine, and solve economic problems in an Islamic way in terms of social, political, economic, and environmental aspects. Islamic economics will always rely on all financial analysis based on the Qur'an, and the Hadith of the Prophet SAW. Islamic economics has three principles, namely tawhid, morality, and balance, that describe welfare. Sustainable development is a planned effort that integrates various environmental, social, and economic aspects into development strategies to ensure society's and the state's well-being. In achieving the goal of sustainable development, the role of Islamic economics is the organization of religious and social institutions, such as zakat institutions and waqf institutions, that can contribute to increased efforts in projects and programs that are not commercially viable but socially important. Islamic finance has much potential to promote sustainable economic development by expanding access to finance (including microfinance), financing infrastructure projects, and expanding the reach of Takaful (Islamic insurance).